Islamic Humanity and Spiritual Balance in the Song Assalamualaikum: Representasi Keseimbangan Islam Kemanusiaan dan Spiritualitas dalam Lagu Assalamualaikum - Muadziana Salsabila Hanifah; Muhammad Yusuf (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Religious songs have increasingly functioned as alternative media for conveying Islamic values within contemporary digital communication. Specific Background: The song Assalamualaikum by Opick communicates religious messages through symbolic lyrics that integrate spirituality, humanity, and everyday social life. Knowledge Gap: However, focused academic analysis of the layered Islamic preaching meanings in this song remains limited, particularly through a semiotic perspective. Aims: This study aims to examine the Islamic preaching messages embedded in the song Assalamualaikum using Roland Barthes’ semiotic framework. Results: Employing a qualitative descriptive approach, the findings show that the song represents a balanced Islamic worldview through three interconnected meanings: the salam as a symbol of prayer and brotherhood, remembrance of God and charity as spiritual responses to life difficulties, and sustained hope for divine forgiveness. These meanings operate across denotative, connotative, and mythological levels, illustrating harmony between devotion to God and social relations. Novelty: This study offers a focused semiotic reading of a single religious song within the context of digital-era da’wah, providing a more specific analytical emphasis than previous studies. Implications: The findings contribute to Islamic communication scholarship by demonstrating how religious music functions as a meaningful medium of contemporary preaching and as a cultural text conveying spiritual and social values simultaneously. Highlights • The song communicates Islamic preaching through layered semiotic meanings• Salam is represented as prayer, brotherhood, and social harmony• Remembrance and charity are framed as spiritual responses to life challenges Keywords Islamic Preaching Message; Religious Song; Semiotic Analysis; Roland Barthes; Islamic Communication